BUDAYA EKOSISTEM SEBAGAI POTENSI PEMBANGUNAN BERWAWASAN KELESTARIAN LINGKUNGAN - Bahar, Mahdi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study discusses the ecosystem cultural issues and their potential for environmentally sound development in the Unitary State of the Republic of Indonesia. Two entities that need to be separated are the epistemological concept of culture and the concept of the state as an organization based on the law (constitution). These two entities are related, and will be explained and made into a conceptual foundation. Basically, communities in Indonesia have local ecosystem wisdom and intelligence as part of cultural system. The conception of local wisdom and intelligence they build is framed in harmony with the natural environment in which they live. Establishment of ecosystem values or norms into culture or tradition has close ties to nature as a source of economy - social welfare. Therefore, the alignment of the environment with the production process (economy) as well as other possibilities in the context of comfort, security, and even religion should be a calculation in taking policy. In certain contexts, sometimes it becomes preserved and even developed into a resource (potential) of development based on cultural sustainability. Keywords— Ecosystem culture, development, environmental sustainability